Plato and Lucretius as philosophical literature - Park, EC (2012)
This thesis compares the interaction of philosophy and literature in Plato and Lucretius. It argues that Plato influenced Lucretius directly, and that this connection increases the interest in comparing them. In the Introduction, I propose that a work of philosophical literature, such as the De Rerum Natura or a Platonic dialogue, cannot be fully understood or appreciated unless both the literary and the philosophical elements are taken into account. In Chapter 1, I examine the tradition of literature and philosophy in which Plato and Lucretius were writing. I argue that the historical evidence increases the likelihood that Lucretius read Plato. Through consideration of parallels between the DRN and the dialogues, I argue that Plato discernibly influenced the DRN. In Chapter 2, I extract a theory of philosophical literature from the Phaedrus, which prompts us to appreciate it as a work of literary art inspired by philosophical knowledge of the Forms. I then analyse Socrates’ ‘prelude’ at Republic IV.432 as an example of how the dialogue’s philosophical and literary teaching works in practice. In Chapters 3 and 4, I consider the treatment of natural philosophy in the Timaeus and DRN II. The ending of the Timaeus is arguably an Aristophanically inspired parody of the zoogonies of the early natural philosophers. This links it to other instances of parody in Plato’s dialogues. DRN II.333-380 involves an argument about atomic variety based on Epicurus, but also, through the image of the world ‘made by hand’, alludes polemically to the intelligently designed world of the Timaeus. Through an examination of Plato’s and Lucretius’ polemical adaptation of their predecessors, I argue that even the most seemingly technical passages of the DRN and the Timaeus still depend upon literary techniques for their full effect. The Conclusion reflects briefly on future paths of investigation.